2022
DOI: 10.1097/meg.0000000000002503
|View full text |Cite
|
Sign up to set email alerts
|

Impact of metformin on the incidence of human cholangiocarcinoma in diabetic patients: a systematic review and meta-analysis

Abstract: Cholangiocarcinoma (CCA) is the second most common liver cancer. Diabetes is a well-known risk factor; however, treatment with metformin has been reported to be protective for several cancers, but data on CCA are still sparse and heterogeneous. We performed this meta-analysis to investigate the role of metformin as a potential protective factor for CCA. In this systematic review and meta-analysis, we searched PubMed/MEDLINE and EMBASE databases, from the date of inception to November 2022, for studies analyzin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In addition, a Chinese and, later, a British meta-analysis confirmed an increased independent risk of iCCA and eCCA in patients with type 2 DM (eCCA OR 1.5; iCCA OR 1.73, respectively) [4,42]. A possible protective role of metformin in the development of CCA has been suggested [37,43], even if further prospective studies are needed.…”
Section: Metabolic Syndromementioning
confidence: 93%
See 1 more Smart Citation
“…In addition, a Chinese and, later, a British meta-analysis confirmed an increased independent risk of iCCA and eCCA in patients with type 2 DM (eCCA OR 1.5; iCCA OR 1.73, respectively) [4,42]. A possible protective role of metformin in the development of CCA has been suggested [37,43], even if further prospective studies are needed.…”
Section: Metabolic Syndromementioning
confidence: 93%
“…Insulin-resistant patients have a higher overall cancer risk due to the mitogenic effect of insulin, which enhances a signaling pathway that activates the transcription of molecules involved in the cell cycle and proliferation [37]. Insulin-resistant patients have a higher overall cancer risk due to the mitogenic effect of insulin, which enhances a signaling pathway that activates the transcription of molecules involved in the cell cycle and proliferation [38,39].…”
Section: Metabolic Syndromementioning
confidence: 99%
“…Various studies showed that the MET is not only capable of decreasing the risk of cancer in patients suffering from diabetes but could also prevent and treat non-diabetic patients suffering from pancreatic, bladder, lung, breast, thyroid, and prostate cancers [10][11][12][13].Besides, MET showed promising results in averting colorectal cancer, squamous cell carcinoma, oral ductal carcinoma in situ , human cholangiocarcinoma, and endometrial cancer [14][15][16][17][18]. Research demonstrates that MET exerts its anticancer effects by activating AMPK, disrupting the crosstalk between the insulin receptor and the G protein-coupled receptor signalling system [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] Besides, MET showed promising results in averting colorectal cancer, squamous cell carcinoma, oral ductal carcinoma in situ, human cholangiocarcinoma, and endometrial cancer. [19][20][21][22][23] Research demonstrates that MET exerts its anticancer effects by activating AMPK, disrupting the crosstalk between the insulin receptor and the G protein-coupled receptor signalling system. 24,25 Also, the direct insulin-independent action of MET by the AMPK activation leads to downregulating of the mammalian target of rapamycin (mTOR) signalling and protein synthesis in tumour cells.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies showed that the MET is not only capable of decreasing the risk of cancer in patients suffering from diabetes but could also prevent and treat nondiabetic patients suffering from pancreatic, bladder, lung, breast, thyroid, and prostate cancers 15–18 . Besides, MET showed promising results in averting colorectal cancer, squamous cell carcinoma, oral ductal carcinoma in situ, human cholangiocarcinoma, and endometrial cancer 19–23 . Research demonstrates that MET exerts its anticancer effects by activating AMPK, disrupting the crosstalk between the insulin receptor and the G protein‐coupled receptor signalling system 24,25 .…”
Section: Introductionmentioning
confidence: 99%